2015
DOI: 10.1680/geot.13.p.218
|View full text |Cite
|
Sign up to set email alerts
|

An approach to enhance efficiency of DEM modelling of soils with crushable grains

Abstract: In this study oedometric compression tests of hydrocarbon coke, Fontainebleau sand and silica sand are simulated in three dimensions using breakable particles. The method adapts a rigorous breakage criterion for elasto-brittle spheres to represent failure of grains isolated between platens or within granular masses. The breakage criterion allows for the effect of particle bulk and contact properties to be treated separately. A discrete fragmentation multigenerational approach is applied as a spawning procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 56 publications
3
103
0
14
Order By: Relevance
“…Although this is one of the more common breakage criteria used in DEM by other researchers, it has often been chosen arbitrarily with no justification, or owing to the theory that the maximum critical stress within a solid sphere is a function only of the maximum contact force (e.g. Chau et al, 2000;Ciantia et al, 2015). However, it was unclear whether this criterion would result in the correct behaviour in DEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is one of the more common breakage criteria used in DEM by other researchers, it has often been chosen arbitrarily with no justification, or owing to the theory that the maximum critical stress within a solid sphere is a function only of the maximum contact force (e.g. Chau et al, 2000;Ciantia et al, 2015). However, it was unclear whether this criterion would result in the correct behaviour in DEM.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate PSDs after shearing appeared realistic, suggesting that their choice of criterion could be appropriate for use in DEM, although they started with an already well-graded distribution. Ciantia et al (2015) also used a criterion of the form F/d 2 , while also considering varying contact area. This was following work by and , who, using a modified Von Mises type criterion (Christensen, 2000) demonstrated that the maximum mobilised stress (not the maximum tensile stress) inside a sphere is a function solely of the largest compressive contact force, occurring almost directly below it, independent of all other contacts.…”
Section: A Review Of Breakage Criteria Used In Demmentioning
confidence: 99%
“…DEM simulations can capture the features of soil behaviour described by the critical state framework: researchers including Ng (2009), Yan & Dong (2011), Guo & Zhao (2013) and Huang et al (2014b) have confirmed that DEM simulations can give a critical state locus, while Hanley et al (2015) and Ciantia et al (2015) have confirmed that DEM simulations of crushable particles can generate a normal compression line. Although DEM has been widely adopted 3 by the soil mechanics community since its inception (O'Sullivan, 2014), energy is not routinely tracked in DEM simulations of quasi-static monotonic tests.…”
Section: Introductionmentioning
confidence: 94%
“…Here, a fractal distribution (Einav, 2007) with maximum particle size smaller 145 than the smallest particle produced during the crushing event is assumed for that purpose. 146 Ciantia et al (2015) detailed this procedure and compared the effect of an alternative 147 splitting configurations on element test response. Authors concluded that the 14-ball crushed 148 configuration represented in Figure 3 (47% volume of mother particle is deleted at each 149 crushing event) was accurate enough to reproduce the macroscopic response of element tests.…”
Section: Particle Splitting and Lost Mass 135mentioning
confidence: 99%
“…As detailed in Ciantia et al (2015), grain-scale information in the form of single particle 309 crushing tests is particularly useful to calibrate crushing variability. This seems especially 310 pertinent in a material with size-dependent internal porosity, because it is expected that 311 microporosity will exert a major influence in grain strength.…”
Section: Calibration 303mentioning
confidence: 99%